Social Dimensions of Antimicrobial Resistance and an Anthropological Approach: Analytic Review - Jawad, M. A. (International Journal of Culture and Religious Studies, 2024)
Purpose: The objective of this paper is to devise a comprehensive and layered framework to tackle antimicrobial resistance (AMR). It aims to weave together the strands of ethnomedicine, healthcare system analysis, and anthropological perspectives on illness, aligning with universal healthcare principles to encourage community participation and address the societal roots of health inequalities. The framework seeks to address AMR through a lens that views health disparities not merely as medical issues, but as complex phenomena shaped by cultural, social, and structural factors. Methodology: The research employs a single-case study design to synthesize and analyse interdisciplinary insights into AMR. This approach facilitates an in-depth understanding of how various elements, such as cultural beliefs, healthcare practices, and community dynamics, interact and influence the spread and management of AMR. By focusing on a single case, the study intends to meticulously document and interpret the nuanced interactions between these factors, providing a detailed narrative that captures the essence of the AMR challenge in a global health context. The study utilizes 66 varied references, such as journal articles, book excerpts, theses, reports, and websites, sourced from academic venues and the internet, published between 1946 and 2023. Findings: Through its investigation, the study presents a healthcare approach that marries the traditional wisdom of ethnomedicine with the precision of biomedicine, underscoring the significance of cultural competence in formulating AMR mitigation strategies. It dissects the intricate relationship between the three primary health sectors"”popular, professional, and folk"”and disentangles the sociocultural concepts of 'disease' and 'illness' as distinguished by medical anthropologists. The research calls for a reconceptualization of healthcare systems that goes beyond the biomedical model, advocating for an integration of the sociocultural, economic, and political dimensions that influence health and illness manifestations. Unique contribution to theory: This study's unique theoretical contribution lies in its interdisciplinary approach to health disparities and AMR. It proposes a model that balances the rigor of scientific research with the insights gleaned from traditional health practices, placing a premium on the dynamics of community involvement and the myriad influences on health. By doing so, it offers a more equitable, sustainable, and contextually relevant paradigm for health practices and policies. This paradigm shift is intended to provide actionable insights for policymakers and health practitioners, enabling them to devise strategies that are not only scientifically sound but also culturally sensitive and broadly applicable. The framework envisages a future where health interventions are tailored to the lived experiences of diverse populations, potentially transforming the landscape of global health and AMR strategy.